2018
DOI: 10.5811/westjem.2018.9.38875
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Administration for Patients with Renal Colic in the Emergency Department Before and After Implementation of an Opioid Reduction Initiative

Abstract: IntroductionWe aimed to evaluate the patterns of analgesic prescribing for emergency department (ED) patients suffering from pain of renal colic before, during, and after implementation of an opioid reduction initiative. We hypothesized that this initiative based on the concept of channels/enzymes/receptors-targeted analgesia would result in overall decrease in opioid utilization in the ED and at discharge.MethodsWe performed a retrospective analysis of ED electronic medical record of patients presenting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Motov and colleagues evaluated the prescribing patterns of physicians treating renal colic following the implementation of an opioid reduction initiative at their institution. 17 The authors observed a 12.7% overall reduction in opioid administration during the ED encounter and a 25.5% reduction in opioid prescribing at discharge. This equated 432 fewer patients receiving opioids while in the ED and 768 fewer patients leaving with an ED prescription.…”
Section: Discussionmentioning
confidence: 93%
“…Motov and colleagues evaluated the prescribing patterns of physicians treating renal colic following the implementation of an opioid reduction initiative at their institution. 17 The authors observed a 12.7% overall reduction in opioid administration during the ED encounter and a 25.5% reduction in opioid prescribing at discharge. This equated 432 fewer patients receiving opioids while in the ED and 768 fewer patients leaving with an ED prescription.…”
Section: Discussionmentioning
confidence: 93%
“…Identifying which diagnosis is associated with higher frequency of opioid prescriptions can be crucial to implementing symptom specific guidelines for opioid prescriptions in an effort to curtail the use of opioids in the ED and upon discharge. A previous study demonstrated a reduction of opioid administration for renal colic after implementation of a opioid-reduction initiative based on pain syndrome-targeted opioid alternative protocols [ 21 ]. Similarly, a number of recent studies have demonstrated a reduction in opioid prescriptions after the implementation of opioid prescribing guidelines for emergency physicians [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid sparing is already recommended in several acute pain pathologies, such as renal colic or low back pain. 5 Likewise, we should focus on ED organization to protect opioid-naive patients from a high risk of opioid misuse.…”
Section: Opioid Reflex At Triage Is Not a Solution For Opioid-naive Patients In Emergency Departmentsmentioning
confidence: 99%